Root developmental adaptation to Fe toxicity: Mechanisms and management - Li, Guangjie; Kronzucker, Herbert J.; Shi, Weiming (Plant signaling & behavior, 2016)
Iron (Fe) is an essential microelement but is highly toxic when in excess. To cope with Fe excess, plants have evolved complex adaptive responses that include morphological and physiological modifications. The highly dynamic adjustments in overall root system architecture (RSA) determine root plasticity and allow plants to efficiently adapt to environmental constraints. However, the effects of Fe excess on RSA are poorly understood. Recently, we showed that excess Fe treatment in Arabidopsis not only directly impairs primary root (PR) growth but also arrests lateral root (LR) formation by acting at the tip of the growing primary root. Such a change is believed to help RSA adjust and restrict excessive Fe absorption in the part of the rhizosphere subject to acute toxicity while maintaining the absorption of other nutrients in the less stressed components of the root system. We further showed that the suppression of PR growth and LR formation under excess Fe is alleviated by K + addition, providing useful insight into the effectiveness of nutrient management to improve RSA and alleviate Fe toxicity symptoms in the field.